Topological essentiality and nonlinear boundary value control problems$^*$ - Górniewicz, Lech; Nistri, Paolo (Topological Methods in Nonlinear Analysis, 1999)
A concept of topological essentiality is used to prove several existenceresults for nonlinear boundary value control problems. Some examples to illustrate the obtained results are presented.